Anti-lactoferrin antibodies and other types of ANCA in ulcerative colitis, primary sclerosing cholangitis, and Crohn's disease. Issue 1 (January 1993) - Peen, E; Almer, S; Bodemar, G; Rydén, B O; Sjölin, C; Tejle, K; Skogh, T
Abstract : Fifty two serum samples from patients with Crohn's disease, 24 from patients with ulcerative colitis, and 12 from patients with primary sclerosing cholangitis were analysed for the presence of anti-neutrophil cytoplasm antibodies (ANCA) of IgG and IgA class by means of enzyme linked immunosorbent assays using lactoferrin, myeloperoxidase, and antigen extracted from azurophil granules, 'alpha antigen' (that is, an antigen preparation containing proteinase 3) as substrates. A high frequency of positive tests for IgG anti-lactoferrin antibodies was found in sera from patients with ulcerative colitis (50%) and primary sclerosing cholangitis (50%). In Crohn's disease only 4 of 52 (8%) sera had anti-lactoferrin antibodies--in all four instances the sera belonged to patients with disease involving the colon. All patients with sclerosing cholangitis and positive tests for anti-lactoferrin had ulcerative colitis. Low levels of IgG antibodies against myeloperoxidase or alpha antigen were also found occasionally in sera from patients with ulcerative colitis and primary sclerosing cholangitis. IgA antibodies directed against lactoferrin and alpha antigen (but not myeloperoxidase) were seen in all three conditions.